Peran Ibu dalam Pendidikan Kesehatan Reproduksi, Peran Bidan, Personal Hygiene Menstruasi terhadap Kejadian Keputihan pada Remaja Putri: The Role of Mothers in Reproductive Health Education, The Role of Midwives, Menstrual Personal Hygiene on the Incidence of Leucorrhea on Young Women - Reza, Chesi Ramadani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: Flour albus is a symptom disorders of the reproductive organs often experienced by most women, according to WHO (World Health Organization) 75% of women in the world will experience vaginal discharge at least once in a lifetime and as many as 45% will have 2 or more. This study aims to determine the relations of mother's role in reproductive health education, role of midwife, personal hygiene menstruation of the teenage girl flour albus event in class VIII and IX at SMP Muhammadiyah 35 Jakarta. Method: This research method uses quantitative research with a cross sectional approach. The study sample used total sampling, namely all the teenage girl in class VIII and IX were 50 people Result: The results showed that there was a relationship between the mother's role in reproductive health education variable and the p-value of 0.003, the role of midwife variable with the result of p- value 0.001 and the variable personal hygiene menstruation with a p-value of 0.015 for the teenage girl flour albus event. Discussion: 34 young women who experience vaginal discharge, 27 young women whose mothers do not play a role in health education, 27 young women who do not get the role of a midwife and 32 young women who are not good at performing menstrual personal hygiene. and there is a relationship between the role of mothers in reproductive health with the incidence of vaginal discharge in adolescent girls. In conclusion it is expected the school to cooperate among parents and health officer, for the reproductive health education, to improve the degree of health and build good reproductive health behavior, as well as to preventing and handling vaginal discharge in teenage girl.